Synthesis, Characterization and Antifungal Activity of Novel Quinazolin-4-one Derivatives Containing 8-Hydroxyquinazoline Ligand and its Various Metal Complexes - R. T. Vashi; S. B. Patel (E-Journal of Chemistry)
Novel ligands containing quinazoline-4-one-8-hydroxyquinoline (QQ) merged moieties were prepared and characterized. For this anthranilic acid and 5-bromoanthranilic acid were converted respectively into 2-chloromethyl–3-(4-methyl phenyl)-3(H)-quinazoline-4-one and 2-chloromethyl–3-(methyl phenyl)-6-bromo-3(H)-quinazoline-4-one. Both these compounds were condensed with 5-amino-8-hydroxyquinoline. The so called resulted compounds were named respectively as 2-[(8-hydroxy-quinolinyl) –5- amino methyl] -3-(4-methylphenyl)- 3(H)- quinazoline -4- one and 2-[(8-hydroxyquinolinyl)-5-aminomethyl] -3(methyl phenyl)-6-bromo-3(H)-quinazoline-4-one. Both the compounds were designated respectively as HL1 and HL2 ligands. The transition metal (Cu2+, Ni2+, Zn2+, Mn2+ and Co2+) complexes of both these ligands were prepared. The ligands and their complexes as case may be were characterized by elemental analysis, spectral studies and number of hydroxyl groups. The stoichiometry of the complexes has been found to be 1:2 (metal: ligand). An octahedral geometry around Co2+, Ni2+ and Mn2+, distorted octahedral geometry around Cu2+ and tetrahedral geometry of around Zn2+ have been proposed. These complexes also been tested for their antifungal activities.